2019
DOI: 10.3390/vaccines7010014
|View full text |Cite
|
Sign up to set email alerts
|

PCV7- and PCV10-Vaccinated Otitis-Prone Children in New Zealand Have Similar Pneumococcal and Haemophilus influenzae Densities in Their Nasopharynx and Middle Ear

Abstract: Otitis media (OM) is a major reason for antibiotic consumption and surgery in children. Nasopharyngeal carriage of otopathogens, Streptococcus pneumoniae and nontypeable Haemophilus influenzae (NTHi), is a prerequisite for development of OM, and increased nasopharyngeal otopathogen density correlates with disease onset. Vaccines can reduce or eliminate otopathogen carriage, as demonstrated for pneumococcal serotypes included in pneumococcal conjugate vaccines (PCV). The 10-valent PCV (PCV10) includes an NTHi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Replacing PCV7 with PCV10 in New Zealand's national immunization program did not result in a decline in NTHi (or S. pneumoniae) prevalence [22]. Neither did it result in a decline in density [24] in the nasopharynx or middle ear of children undergoing tympanostomy tube insertion for recurrent AOM/OM with effusion (or in the nasopharynx of non-otitis-prone children). In contrast, a decreased prevalence of NTHi-infected ear discharge in PCV10-vaccinated Aboriginal children compared to PCV7-vaccinated Aboriginal children was observed when PCV10 was used in the Northern Territory of Australia from 2009 to 2011 [23].…”
Section: Impact Of Current Vaccines On Ommentioning
confidence: 95%
“…Replacing PCV7 with PCV10 in New Zealand's national immunization program did not result in a decline in NTHi (or S. pneumoniae) prevalence [22]. Neither did it result in a decline in density [24] in the nasopharynx or middle ear of children undergoing tympanostomy tube insertion for recurrent AOM/OM with effusion (or in the nasopharynx of non-otitis-prone children). In contrast, a decreased prevalence of NTHi-infected ear discharge in PCV10-vaccinated Aboriginal children compared to PCV7-vaccinated Aboriginal children was observed when PCV10 was used in the Northern Territory of Australia from 2009 to 2011 [23].…”
Section: Impact Of Current Vaccines On Ommentioning
confidence: 95%
“…The swab media was enzymatically lysed and genomic DNA (gDNA) extracted as previously described ( 35 ). Quantitative (q)PCR was conducted using primers and probes specific for S. pneumoniae: lytA ( 36 ), and H. influenzae: fuc P and hpd 3 as described previously ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from IPD, non-invasive pneumococcal disease, such as acute otitis media (AOM) and community-acquired pneumonia (CAP) cause significant childhood and adult morbidity. A study by De Gier et al examined the effect of PCV10 and PCV13 on nasopharyngeal carriage of pneumococcus and non-typeable Haemophilus influenza (NTHi), which are a prerequisite for the development of AOM [4]. The authors found that PCV10 does not result in the reduction of NTHi carriage and is associated with higher pneumococcal carriage compared to PCV13.…”
mentioning
confidence: 99%